ANALISIS PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN - Agus Suryanto; Refianto Refianto (STIE Wiyatamandala, 2019)
This research examines empirically the effect of implementation good corporate governance on firm’s financial performance of manufacturing companies. There are several aspects and dimensions of corporate governance, which may influence a firm’s performance but this study focused on four aspects namely Audit Committee, Board’s Independence, Institutional Ownership, and Managerial Ownership. Firm financial performance has been measured through Return On Asset (ROA). According to this logic, we hypothesize that is significant effect on the institutional ownership of firm’s financial performance. Other variables the audit committee, board’s independence, managerial ownership of firm’s performance have no effect on company ROA. And the audit committee, board’s independence, institutional ownership, managerial ownership positively affect of firm’s financial performance simultaneously.